Modelagem matemática por meio de Sistemas Fuzzy: um Instrumento para avaliação de autismo - Zago, Lucas de Agostini (2019)
In this work, concepts, definitions and theorems about Fuzzy Logic and Systems Based on Fuzzy Rules were presented. We used these systems to develop a mathematical model for diagnosing autism based on the CARS-BR scale: without autism, mild / moderate autism, and severe autism. The choice is due to the great subjectivity involved in the medical diagnosis process of behavioral syndromes.